When push comes to shove: The impact of the 2008 global financial crisis on households of Paete, Laguna - Abao, Carmel V (Archīum Ateneo, 2012)
This volume focuses on the Asian financial crisis of the late 1990s and the 2008 financial crisis that originated in the United States. How have these crises affected Asia? How has Asia coped? What has been the impact of the crises on ordinary people? Between the covers of this book are theoretical perspectives on financial crises, followed by specific studies on the crises’ impact on Filipino overseas workers and the responses of families with overseas workers in Paete, Laguna; the effects of the crises on the Indonesian pirates; the connection of an economic framework between Taiwan and China to the financial crisis; and the impact and responses of business firms in selected countries in ASEA + 3.